China : Strengthening Monetary Policy Implementation - Laurens, Bernard (IMF Working Papers; Working Paper, 2007)
The People's Bank of China (PBC) has made great strides in modernizing its monetary policy frameworks but their effectiveness will diminish as the sophistication of the economy increases. Empirical evidence supports maintaining a reference to money in China's monetary strategy and enhancing the role of interest rates in its conduct. We advocate adoption of an eclectic strategy involving the monitoring of several indicators, and of a short-term interest rate as the operational target. The PBC should be granted discretion to change its policy rate, and there are no technical obstacles for such a move to occur in the near future.